2020
DOI: 10.1177/1758835920982853
|View full text |Cite
|
Sign up to set email alerts
|

ATR and p-ATR are emerging prognostic biomarkers and DNA damage response targets in ovarian cancer

Abstract: Background: Although ataxia-telangiectasia and Rad3 related (ATR) has an established role in the DNA damage response of various cancers, its clinical and prognostic significance in ovarian cancer remains largely unknown. The aims of this study were to assess the expression, function, and clinical prognostic relationship of ATR and phospho-ATR ser428 (p-ATR) in ovarian cancer. Methods: We confirmed ATR and p-ATR expression by immunohistochemistry (IHC) in a unique ovarian cancer tissue microarray constructed of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Importantly, ATR was regarded as the primary sensor of oncogenes that triggered replication stress and DNA damage. Previous studies revealed that ATR was likely to be a prognostic biomarker for some solid tumors (Feng et al, 2020), but the result was contradictory found by Zighelboim et al (2009). Kashyap et al (2020) found that ATR presented with a low transcriptional level in 76% of uveal melanoma patients who were significant with metastasis (p = 0.046).…”
Section: Discussionmentioning
confidence: 91%
“…Importantly, ATR was regarded as the primary sensor of oncogenes that triggered replication stress and DNA damage. Previous studies revealed that ATR was likely to be a prognostic biomarker for some solid tumors (Feng et al, 2020), but the result was contradictory found by Zighelboim et al (2009). Kashyap et al (2020) found that ATR presented with a low transcriptional level in 76% of uveal melanoma patients who were significant with metastasis (p = 0.046).…”
Section: Discussionmentioning
confidence: 91%
“…ATRCHK1 pathway activation is increased in various tumor types [ 198 , 199 ]. Furthermore, elevated ATR protein, phospho-ATR, and phospho-CHK1 expression are associated with a poor prognosis in bladder, ovarian, and breast cancers [ 199 , 200 , 201 ]. Because the ATR kinase controls H 2 S concentrations, increases in ATR and CHK1 may increase H 2 S production.…”
Section: H 2 S and Dna Repairmentioning
confidence: 99%
“…Low cellular H 2 S concentrations increased ATR kinase activity measured by CHK1 phosphorylation, while high H 2 S concentrations suppressed ATR ser-435 phosphorylation, a marker of ATR kinase activation [ 4 , 96 ]. Increased ATR-CHK1 pathway activity has been identified in several tumor types [ 97 , 98 , 99 , 100 ]. Additionally, increased ATR protein, phospho-ATR, and phospho-CHK1 expression confers a poor prognosis in breast, bladder, and ovarian cancers [ 98 , 99 , 100 ].…”
Section: H 2 S and Nuclear Dna Repairmentioning
confidence: 99%
“…Increased ATR-CHK1 pathway activity has been identified in several tumor types [ 97 , 98 , 99 , 100 ]. Additionally, increased ATR protein, phospho-ATR, and phospho-CHK1 expression confers a poor prognosis in breast, bladder, and ovarian cancers [ 98 , 99 , 100 ]. As the ATR kinase regulates H 2 S concentrations, it is possible that increases in ATR and CHK1 result in increased H 2 S synthesis.…”
Section: H 2 S and Nuclear Dna Repairmentioning
confidence: 99%